Annual international conference on kinesiology and exercise sciences - Saha, Soumendra (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2012)
Twenty-three world-class cricket players of Bangladesh, selected for the ICC World Cup 20 II, were compared with twenty-two amateur-competitive and eighteen developmental level cricketers of South-Asian contingent, on the basis of their consistent high performance and on the basis of their performance on psychomotor and psychobiological parameters, volunteered in this study. Orienting reflex measures of skin conductance as well as cardiovascular activity were done while the cricketers were engaged in psychomotor performances. Whole body reaction ability and anticipation simulated with close-fielding performance in cricket were evaluated as measure of agility and anticipation, along with the evaluations of signal detection type of perceptual discrimination ability (as measure of cognitive competence). Structural equations were Abstract done to identify the path regression related to performance excellence, which were suggestive of incoherence between the predictors. Short-tenn intensive action-regulation training was introduced, which could in tum modify intrinsic psychobiological mechanism leading towards excellence in performance in the elite-level cricket players. Multiple linear and polynomial regression analyses along with the predictive structural analyses were done to identify relationships between the psychobiological processes explained by the HPA axis and the TCA pathways, in relation to the cognitive-affective and affective-motivational aspects of sports behaviour, revealed by the projective analyses of emotionality. These models were aptly able to explain the efficacy of the action-regulation intervention techniques, in inducing the cognitive and emotional flexibility required for performance excellence in elite-level cricket events.